The Role of Optimism as a Mediator of the Influence of Social Support on Antiretroviral (ARV) Treatment Adherence in ODHIV - Rahmah, Sitti; Tetteng, Basti (Universitas Negeri Makassar, 2025)
Abstract. This study aims to examine the role of optimism as a mediator in the relationship between social support and adherence to antiretroviral (ARV) treatment among people living with HIV (PLHIV). The study involved 53 respondents who had undergone at least one follow-up visit, selected from Gaya Celebes Foundation, the Peer Support Concern Foundation (YPKDS), the Indonesian Positive Women Association (IPPI), and Kassi-Kassi Community Health Center. Data collection was conducted using the Morisky Medication Adherence Scale (MMAS), the Multidimensional Scale of Perceived Social Support (MSPSS), and the Revised Life Orientation Test (LOT-R). The results of SEM analysis showed: (1) a significant effect of social support on treatment adherence (f=0.367; t=3.803; p=0.000); (2) a significant effect of optimism on treatment adherence (f=0.186; t=2.476; p=0.013); (3) a significant effect of social support on optimism (f=0.295; t=5.130; p=0.000); and (4) a significant effect of social support on treatment adherence mediated by optimism (t=2.057; p=0.040) with a total upsilon (v) of 0.026. These findings indicate that social support influences ARV treatment adherence among PLHIV, and this influence is strengthened when optimism acts as a mediator. Keywords: Optimism, Social Support, Treatment Adherence, ODHIV